Managers and Leaders in Need of Entrepreneurial Competences - Agnieszka Postuła; Julita Majczyk (Entrepreneurial Business and Economics Review)
Objective: The purpose of this article is to provide insight into how managers fit their roles and what tasks they perform. It addresses leaders and action they undertake. In particular, the study aims to focus on competences which comprise specific skills and experience, knowledge, and cognitive abilities to understand, analyse, or reason.